Hypocretinergic Control of Spinal Cord Motoneurons - Yamuy, Jack (J Neurosci, 2004)
Hypocretinergic (orexinergic) neurons in the lateral hypothalamus project to motor columns in the lumbar spinal cord. Consequently, we sought to determine whether the hypocretinergic system modulates the electrical activity of motoneurons. Using in vivo intracellular recording techniques, we examined the response of spinal motoneurons in the cat to electrical stimulation of the lateral hypothalamus. In addition, we examined the membrane potential response to orthodromic stimulation and intracellular current injection before and after both hypothalamic stimulation and the juxtacellular application of hypocretin-1. It was found that (1) hypothalamic stimulation produced a complex sequence of depolarizing- hyperpolarizing potentials in spinal motoneurons; (2) the depolarizing potentials decreased in amplitude after the application of SB-334867, a hypocretin type 1 receptor antagonist; (3) the EPSP induced by dorsal root stimulation was not affected by the application of SB-334867; (4) subthreshold stimulation of dorsal roots and intracellular depolarizing current steps produced spike potentials when applied in concert to stimulation of the hypothalamus or after the local application of hypocretin-1; (5) the juxtacellular application of hypocretin-1 induced motoneuron depolarization and, frequently, high-frequency discharge; (6) hypocretin-1 produced a significant decrease in rheobase (36%), membrane time constant (16.4%), and the equalizing time constant (23.3%); (7) in a small number of motoneurons, hypocretin-1 produced an increase in the synaptic noise; and (8) the input resistance was not affected after hypocretin-1. The juxtacellular application of vehicle (saline) and denatured hypocretin-1 did not produce changes in the preceding electrophysiological properties. We conclude that hypothalamic hypocretinergic neurons are capable of modulating the activity of lumbar motoneurons through presynaptic and postsynaptic mechanisms. The lack of hypocretin-induced facilitation of motoneurons may be a critical component of the pathophysiology of cataplexy.